PENGARUH METODE ROLE PLAYING TERHADAP HASIL BELAJAR BAHASA INDONESIA MATERI DRAMA PADA SISWA KELAS V SEKOLAH DASAR - Ahsanul Huda Susanto; Yenny Widyawati; Nining Setyaningsih; Sumardi, Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The results of learning Indonesian in the speaking aspect are still low. The aim of this research is to determine the influence of the role playing method on the results of learning Indonesian drama material in class V elementary school students. This research was conducted using a comparative quantitative approach with a quasi-experimental design. The sample in this study involved two classes, namely the VA SD N 04 Karangsari, Jatiyoso, Karanganyar class with 25 students as the experimental class and the VB class with 25 students as the control class. Data was collected using observation, tests, documentation and questionnaire techniques. Data were analyzed using descriptive statistical techniques and hypothesis testing using the t-test. The results of the research show that the average post-test score is 88.4 and after testing the t statistic on the post-test t data, it is obtained that t count > t table, namely 4.341 > 2.011 (n = 25) with a significance level of 0.05 or 5% which is stated accepting Ha and rejecting Ho. This means that in the experimental class, the role playing method had a significant effect on the students' learning outcomes in Indonesian drama material.